Borders - King, Thomas, 1943- (Boston : Little, Brown and Company, 2022)
A boy and his mother leave their reservation in Canada to visit the boy's sister in Salt Lake City. But when his mother refuses to identity themselves as American or Canadian at the border, and instead claims their citizenship as Blackfoot, they become caught between the two borders.